Monocytes and dendritic cells are the primary sources of interleukin 37 in human immune cells. Issue 4 (23rd November 2016) - Rudloff, Ina; Cho, Steven X.; Lao, Jason C.; Ngo, Devi; McKenzie, Matthew; Nold‐Petry, Claudia A.; Nold, Marcel F.
Abstract : IL‐37 is produced and secreted by antigen‐presenting cells, including monocytes and DCs, where IL‐37 may act as an alarmin. Abstract : The interleukin (IL)‐1 family member IL‐37 is one of few anti‐inflammatory cytokines, and it is capable of countering a broad spectrum of proinflammatory assaults. Although it is known that leukocytes are a major source of IL‐37, knowledge on IL‐37 production and secretion in specific immune cell types remains limited. Thus, we investigated IL‐37 mRNA expression as well as protein production and secretion in human PBMCs. In PBMCs stimulated with agonists of Toll‐like receptors (TLRs) 1–6 and 9, IL1F7 (the IL‐37‐encoding gene) was induced up to 9‐fold, peaked at 6–8 h and returned to steady‐state at 72 h. LPS‐induced IL1F7 expression comprised isoforms b and c but not a and e . Flow cytometry revealed that among IL‐37 + PBMCs, monocytes predominated (81–91%), but T cells (6–8%) and myeloid dendritic cells (mDCs, 1–2%) also contributed to the IL‐37 + leukocyte pool. Monocytes and mDCs, but not T cells, were capable of secreting IL‐37. Whereas monocytes and mDCs secreted IL‐37 upon LPS stimulation, only mDCs also released IL‐37 at steady‐state. Among monocyte subsets, IL‐37 was LPS inducible and secreted only in classical and, although less pronounced, in intermediate monocytes; secretion was observed as early as 3 h after stimulation. Overall, our data suggest that constitutive IL‐37 secretion by mDCs may serve to maintain an anti‐inflammatory milieu at steady state, whereas IL‐37 is stored in monocytes to be available for rapid release upon inflammatory encounters, thus acting as a novel anti‐inflammatory alarmin. These insights may prove important to advancing towards clinical use the protective functions of one of the most powerful anti‐inflammatory mediators so far discovered.